If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 15 = 13t Reorder the terms: 15 + 3t = 13t Solving 15 + 3t = 13t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13t' to each side of the equation. 15 + 3t + -13t = 13t + -13t Combine like terms: 3t + -13t = -10t 15 + -10t = 13t + -13t Combine like terms: 13t + -13t = 0 15 + -10t = 0 Add '-15' to each side of the equation. 15 + -15 + -10t = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -10t = 0 + -15 -10t = 0 + -15 Combine like terms: 0 + -15 = -15 -10t = -15 Divide each side by '-10'. t = 1.5 Simplifying t = 1.5
| 7(a+3)=4a | | 10m(4m-9)=30 | | y^2+8y=4 | | 8(w-6)=2w | | 2x-45=43-2 | | 6*(3x-7)-12-4x=9x-(7x+6) | | x-7-7x=5 | | 10u-20=9u-11 | | 3(a+2)=a+12 | | 8s^2-30s+18= | | 16m^2-1=15m | | 2x^2-25x+36=0 | | X^2-1x-1=0 | | 6a^2-19a+15= | | -6n+10=-4n-18 | | 7y-10=5y-2 | | -6x-9y=54 | | (9m^3+4n)+7m^3= | | 21-11=5(x-1) | | 8-9x=104-37x | | 6x-2=x-0 | | 6f-14+26-3f-15f= | | -6x+2=1 | | -121-8x=8x+23 | | y^2+3y-16=y-1 | | 3(y-2)=12 | | X^2+19x+K= | | -x=3+2x+16 | | 68=-4(5x+3) | | -10x-106=29-5x | | -21(3t)= | | 28m^2+28m-56=0 |